2023
DOI: 10.3390/jof9020165
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tannin Tolerant Non-Saccharomyces Yeasts Isolated from Miang for Production of Health-Targeted Beverage Using Miang Processing Byproducts

Abstract: This research demonstrated an excellent potential approach for utilizing Miang fermentation broth (MF-broth), a liquid residual byproduct from the Miang fermentation process as a health-targeted beverage. One hundred and twenty yeast strains isolated from Miang samples were screened for their potential to ferment MF-broth and four isolates, P2, P3, P7 and P9 were selected, based on the characteristics of low alcoholic production, probiotic properties, and tannin tolerance. Based on a D1/D2 rDNA sequence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…Similarly, Chuengcharoenphanich et al [59] also noted that C. rhodanensis possesses the capability to produce endoglucanase, exoglucanase and β-glucosidase enzymes. Furthermore, the work of Kodchasee et al [10] supports this, highlighting that C. rhodanensis isolated from Miang has the capacity to produce extracellular β-glucosidase enzymes. Additionally, it is noteworthy that at both 37 and 45 • C during enzyme production, yeast cells presented higher extracellular β-glucosidase and CMCase activities.…”
Section: Investigation Of β-Glucosidase and Cmcase Production By C Rh...mentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, Chuengcharoenphanich et al [59] also noted that C. rhodanensis possesses the capability to produce endoglucanase, exoglucanase and β-glucosidase enzymes. Furthermore, the work of Kodchasee et al [10] supports this, highlighting that C. rhodanensis isolated from Miang has the capacity to produce extracellular β-glucosidase enzymes. Additionally, it is noteworthy that at both 37 and 45 • C during enzyme production, yeast cells presented higher extracellular β-glucosidase and CMCase activities.…”
Section: Investigation Of β-Glucosidase and Cmcase Production By C Rh...mentioning
confidence: 80%
“…This discovery broadens the potential industrial applications of C. rhodanensis as tannase has various uses in food processing and pharmaceuticals. In addition, the study by Kodchasee et al [10] revealed that C. rhodanensis displays the dual capability of not only synthesizing the β-glucosidase enzyme but also producing esters, which are essential components in the process of wine production. The metagenomics analysis reported by Bo et al [4] revealed that the yeast Cyberlindnera sp.…”
Section: Molecular Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…S. cerevisiae ML1-2 showed significant advantages in growth and enhanced contents of ethanol, polyphenols, tannin, and flavonoids compared to a reference strain, S. cerevisiae TISTR 5088 [9]. Additionally, the use of tannin-tolerant non-Saccharomyces yeast isolated from Miang, such as Wikerhamomyces anomalus and Cyberlindnera rhodanensis, from the fermentation of Miang residual broth provided different volatile organic compound profiles, with elevated levels of ester groups like ethyl acetate and isoamyl acetate [10].…”
Section: Introductionmentioning
confidence: 99%